Functional outcome of diaphyseal humerus fractures treated with LCDCP and intramedullary nail - a comparative study - Elango M; Manoharan M; Sureshraj P; Justin Moses C; Murugan A (International Journal of Medical Research and Review, 2015)
Background-Diaphyseal humerus fractures are not uncommon in orthopedics; accounting for approximately 3% of all fractures and represent 20% of all humeral fractures. Most of the humeral shaft fractures are best treated non-operatively with fairly high union rates. With recent advances, encouraging results following internal fixation had led to the expansion of surgical indications. But again the right procedure and implant of choice, remains controversial. Usual surgical modalities include compression plating (DCP) and intramedullary nailing (IMN). Literature review states that previous studies comparing these two implants have came out with varying results.Objective-The objective of this study is to compare the functional outcome of adult diaphyseal humerus fractures treated by limited contact dynamic compression plating and intramedullary interlocked nailing.Materials and methods- We prospectively randomised twenty eight patients with closed diaphyseal humerus fractures presented to our hospital, over a period of two years and operated with either limited contact dynamic compression plate (LC-DCP) or Intramedullary interlocked nail (IMIL). A minimum of six months follow-up period was completed only by twenty four patients with twelve in each group. Functional scoring was done based on the Rodriguez-Merchan criteria at 4, 8, 12 and 24 weeks for all the patients.Results & Conclusion-Our findings showed subtle differences favouring the nailing group, yet statistically it turned out to be insignificant. We conclude that none of the implant is superior to other, in terms of fracture union and functional outcome. Hence the implant choice should be at the discretion of the operating surgeon.